2014
DOI: 10.1021/nl502570f
|View full text |Cite
|
Sign up to set email alerts
|

Metal Seed Layer Thickness-Induced Transition From Vertical to Horizontal Growth of MoS2 and WS2

Abstract: Two-dimensional (2D), layered transition metal dichalcogenides (TMDCs) can grow in two different growth directions, that is, horizontal and vertical. In the horizontal growth, 2D TMDC layers grow in planar direction with their basal planes parallel to growth substrates. In the vertical growth, 2D TMDC layers grow standing upright on growth substrates exposing their edge sites rather than their basal planes. The two distinct morphologies present unique materials properties suitable for specific applications, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
308
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(333 citation statements)
references
References 27 publications
24
308
1
Order By: Relevance
“…For example, it has been shown that the conversion of metallic Mo (and W) films to MoS 2 (WS 2 ) can lead to horizontal or vertical stacking of the resulting layered materials, depending on the metal film thickness. 35 Table S4), we find low m* for SnS, suggesting high electron mobility in the phonon-scattering limited regime. Quantum transport calculations show a pronounced anisotropy in the in-plane conductance of Sn 2 S 3 , whereas basal-plane oriented SnS has anisotropic conductance within a narrower energy range and the conductance in SnS 2 is nearly perfectly isotropic, similar to TMDs such as MoS 2 ( Fig.…”
Section: Comparison Ofmentioning
confidence: 82%
“…For example, it has been shown that the conversion of metallic Mo (and W) films to MoS 2 (WS 2 ) can lead to horizontal or vertical stacking of the resulting layered materials, depending on the metal film thickness. 35 Table S4), we find low m* for SnS, suggesting high electron mobility in the phonon-scattering limited regime. Quantum transport calculations show a pronounced anisotropy in the in-plane conductance of Sn 2 S 3 , whereas basal-plane oriented SnS has anisotropic conductance within a narrower energy range and the conductance in SnS 2 is nearly perfectly isotropic, similar to TMDs such as MoS 2 ( Fig.…”
Section: Comparison Ofmentioning
confidence: 82%
“…It is well known that the amount of catalytic active sites along the edges of MoS2 is one of the key factors for the hydrogen evolution reaction (HER). It is enhanced heavily by growing MoS2 thin films with vertically aligned layers in previous reports [17,18]. Recently, Our group reported the underlying formation mechanism of SF-MoS2 [19], where the number of edges increased heavily [14,20].…”
Section: Introductionmentioning
confidence: 77%
“…For normal (OF-) MoS 2 , the two characteristic modes E' and A' 1 are located at 382.5 (383.7) and 402.9 (402.9) cm −1 , respectively, indicating both samples are in high quality. Although it is reported that the intensity ratio between E' and A' 1 mode decreases with the amount of exposed 2D edge sites when the MoS 2 plane is vertical to the substrate due to the polarization dependence [17,18], we do not observe noticeable ratio difference for the three specimen (0.65, 0.66 and 0.60 for normal, OFand SF-MoS 2 , respectively), which can be attributed to the MoS 2 plane parallel to the substrate. Table 1 summarizes the positions of Raman modes for 1H-(normal), OF-, SF-and 1T/1T'-MoS 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the growth conditions, two types of crystal orientations were obtained, with the basal plane of the crystallites being predominantly oriented either in parallel or perpendicular directions relative to the substrate surface. Recently, a rapid sulfurization/ selenization process to convert Mo and W thin films into polycrystalline molybdenum dichalcogenide films was also demonstrated, where sulfur/selenium powders as the precursors and Ar as a carrier gas were used [29][30][31]. Due to chemically reactive edge sites, such structures are useful as an active material for catalytic reactions [32,33].…”
Section: Main Textmentioning
confidence: 99%